Superior Sternal Cleft – A Rare Congenital Anomaly Associated with Atrial Septal Defect - Obu, Dorathy Chinwe; Ezeanosike, Obumneme Benaianh; Nwukor, Samuel Amechi; Arua, Onyinyechukwu Adaeze; Ezeanwu, Achike (Archives of Clinical and Medical Case Reports, 2020)
The sternal cleft is a rare anomaly occurring in 1 in 50, 000 – 100, 000 births. It results from either partial or total failure of sternal fusion early in embryological development. A few causes such as riboflavin deficiency, alcohol abuse during pregnancy, and disruption in the HOX-B4 gene have been postulated. Although asymptomatic, clinical diagnosis is easily made at birth due to the obvious chest defect and abnormal movements of the thorax. Surgery is indicated to prevent mediastinal injury, respiratory and hemodynamic sequelae, allow optimal growth of the chest, and cosmesis. We report a case of superior sternal cleft and skin defect associated with isolated ostium secundum type of atrial septal defect in an apparently healthy term female newborn. This is to create awareness among Paediatricians on this very rare type of congenital anomaly that should warrant further investigation for aetiologies and full evaluation in Nigeria. Also, to share the knowledge that will aid counseling of affected families because of possible environmental/social causes, and concerning recurrence in other siblings due to a genetic predisposition. <gdiv></gdiv>